Mental healthcare users' perceptions of mental health services at a primary healthcare level - Zwane, Siphelele (Rhodes University, Faculty of Humanities, Department of Psychology)
This study interrogates the complexities of mental healthcare in primary healthcare settings, focusing on the experiences and perceptions of participants within the Makana municipality in the Eastern Cape Province, which is characterised by a low socio-economic status. The matter of mental healthcare is of great significance within the context of South Africa, a country grappling with multifaceted challenges. Over the years, mental health has progressed from being marginalised to being more widely acknowledged. While the integration into tertiary and urban healthcare settings has become smoother, primary healthcare has encountered numerous obstacles. This presents a concern, due to the socioeconomic difficulties faced by individuals accessing primary care, which predispose them to mental health issues. Consequently, it is imperative to conduct research focusing on the experiences and perspectives of mental healthcare users within primary healthcare, a relatively underexplored area. The primary objective of the current research study was to contribute to the existing knowledge base, providing valuable insights for relevant stakeholders and policymakers, such as the National Mental Health Policy Framework 2023-2030, to reference when formulating strategies to enhance the integration of mental healthcare into primary healthcare. The study used purposive sampling to interview mental healthcare users within the Makana municipality. Employing a qualitative design facilitated in-depth dialogue between the participants and the researcher, generating valuable data. Thematic Analysis was employed to analyse and present meaningful data, providing an overview of the participants' shared experiences. The study identified four significant themes: the utility of primary health clinic; the urgent need for mental health education; socioeconomics, and mental health, and the complex dynamics of help-seeking behaviours. The findings underscore the pressing need to integrate quality mental health into PHC, emphasising the importance of mental health education, increased resources, task-sharing, and the prioritisation of both physical and mental illnesses.
Keywords: Mental health services -- South Africa -- Makhanda; Primary care (Medicine); Mental health consumer; Mental health education -- South Africa; Help-seeking